Mean-reverting market model: speculative opportunities and non-arbitrage - Dokuchaev, Nikolai (Chapman & Hall (Taylor & Francis), 2011)
The paper studies arbitrage opportunities and possible speculative opportunities for diffusion mean-reverting market models. It is shown that the Novikov condition is satisfied for any time interval and for any set of parameters. It is non-trivial because the appreciation rate has Gaussian distribution converging to a stationary limit. It follows that the mean-reverting model is arbitrage-free for any finite time interval. Further, it is shown that this model still allows some speculative opportunities: a gain for a wide enough set of expected utilities can be achieved for a strategy that does not require any hypothesis on market parameters and does not use estimation of these parameters.